(untitled) (Acta Scientiarum. Technology, 2021)
Water-soluble mucilage extracted from flaxseed has excellent hydrocolloid potential in gel formation; moreover, it can become a product of high technological value in the food, pharmaceutical and cosmetic industries because it has high viscosity in aqueous solution. The aim of the current study is to investigate the effect of extraction medium pH on extraction yield and soluble fiber content. In addition, the purification step effect was evaluated through Fourier transform infrared spectroscopy (FTIR). Extractions were carried out at 3 different pH values (3.81, 6.75 and 9.69) for 13.25 h at 45 oC. The highest yield was recorded at pH 6.75; the highest soluble fiber content was found at pH 3.81. It was possible seeing that the extraction of flaxseed macromolecules in basic medium (pH 9.69) presented the best quality in comparison to other extractions. The purification step based on precipitation with ethanol did not fully remove impurities from the samples.